The Influence of Algal Exudate on the Hygroscopicity of Sea Spray Particles. (1st July 2010) - Wex, H.; Fuentes, E.; Tsagkogeorgas, G.; Voigtländer, J.; Clauss, T.; Kiselev, A.; Green, D. H.; Coe, H.; McFiggans, G.; Stratmann, F.
Abstract : We examined the effect of organic matter released by four different algal species on the hygroscopic growth and droplet activation behaviour of laboratory-generated marine aerosol particles. Hygroscopic growth factors and dry diameters for activation were reduced by less than 10%, compared to that of sodium chloride or of artificial seawater that was devoid of marine surfactants. Concentration-dependent nonideal behaviour was observed for the artificial seawater. But within measurement uncertainty, the measured hygroscopic growth and droplet activation behaviour for the samples that contained organic matter were consistent with a hygroscopicity parameter that was constant between the sub- and supersaturated measurement points. Also, the hygroscopic growth measured for hydrated particles after 3 and after 10 seconds was similar, which implies that in this time range no kinetic effects were detected.